A high resolution melting real time PCR for mapping of filaria infection in domestic cats living in brugian filariosis-endemic areas - Sirichit Wongkamchai (2018)
We present here a real time PCR with high resolution melting (HRM) analysis for determining the prevalence and distribution of filarial species in domestic cats residing in brugian filariosis endemic areas of Narathiwat province, Thailand. Filarial species can be clearly distinguished in a single well using a single pair of primers. Blood samples were taken from a total of 2039 domestic cats living in endemic areas. Microfilariae were detected in 5.7% of the sample, while the overall prevalence of filaria infection by HRM analysis was 6.6%. The filariae species found in the infected cats were Brugia malayi, Dirofilaria immitis, D. repens as well as Acanthocheilonema (Dipetalonema) reconditum. This is the first report of A. reconditum infection from Thailand. The study also observed an overlapping of the distribution areas of animal and human filariae. From a public health perspective, the distribution and prevalence of these nematodes warrant an appropriate drug-based prophylaxis to be administered to cats in the endemic areas to reduce the number of diseased carriers. Furthermore, this molecular approach is more sensitive than microfilariae detection, enables species identification and greatly facilitates the collection of epidemiological data. Thus, the present study may help to bridge human-animal interface by coordinating research outcomes with the control of zoonoses that is vitally important for human and veterinary public health. © 2013 Elsevier B.V.